2014
DOI: 10.1002/macp.201300749
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Polyethylene‐Bound Antioxidants

Abstract: Four novel well‐defined polyethylene‐bound antioxidants (PE‐bound antioxidants) with distinct secondary structures are synthesized via transesterification reactions between methyl 3‐(3,5‐di‐tert‐butyl‐4‐hydroxyphenyl)propionate and hydroxyl‐terminated polyethylenes. The results of thermal gravimetric analysis under an air atmosphere demonstrate that the thermal stabilities of PE‐bound antioxidants are higher than that of commercial antioxidant Irganox1076 and are strongly related to their chemical structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 70 publications
(107 reference statements)
2
40
0
Order By: Relevance
“…Previously, we demonstrated that chain end functionalized PE, such as diol‐ and triol‐terminated PE, could be facilely prepared via epoxide ring‐opening reaction between epoxide‐terminated PE (e‐PE) and nucleophilic reagents (Red‐Al, diethanolamine and N ‐methylethanolamine etc.) . We also showed that chain end functionalized PE (trimethoxysilane‐terminated PE) is useful in the surface modification of carbon nanotube, a carbon‐based nanomaterial, and that modified carbon nanotube could be homogeneously dispersed in a low density PE matrix since the interfacial interactions between the carbon nanotube and PE matrix were efficiently enhanced .…”
Section: Introductionmentioning
confidence: 85%
“…Previously, we demonstrated that chain end functionalized PE, such as diol‐ and triol‐terminated PE, could be facilely prepared via epoxide ring‐opening reaction between epoxide‐terminated PE (e‐PE) and nucleophilic reagents (Red‐Al, diethanolamine and N ‐methylethanolamine etc.) . We also showed that chain end functionalized PE (trimethoxysilane‐terminated PE) is useful in the surface modification of carbon nanotube, a carbon‐based nanomaterial, and that modified carbon nanotube could be homogeneously dispersed in a low density PE matrix since the interfacial interactions between the carbon nanotube and PE matrix were efficiently enhanced .…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, the reaction conditions are harsh, and the post‐treatment is relatively complicated. The other one is to directly synthesize macromolecular antioxidants with the reactive monomers containing antioxidative groups or chemically graft antioxidative groups onto organic backbones with high molecular weight . Beer et al .…”
Section: Introductionmentioning
confidence: 99%
“…This approach is particularly acute in thin film and coating applications. However, there are only few reports [12][13][14][15] discussing PE and PP-bonded hindered phenol antioxidants. Most synthesis routes are based on free-radical mediated copolymerization and grafting reactions with monomers containing hindered phenol moieties [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%